Genre and motif variations in Biliran folk narratives: Insights for literary and cultural studies - A. Niez, Roland (Edelweiss Applied Science and Technology, 2024)
Biliran folksongs, folktales, and various forms of folk narratives from the elderly will be documented to help safeguard the dwindling oral tradition. This study aims to contribute to the preservation and conservation of the vibrant and genuine cultural legacy of oral traditions in the Philippines. Utilizing the Biliran folk narratives as a corpus and triangulating these with interview data from participants, deductive content analysis, discourse analysis, and thematic analyses were applied to analyze and generate data and results. The genres of the twenty-one (21) folk narratives from various towns or municipalities included six (6) myths, ten (10) folktales, and five (5) legends. The predominant motifs were magic, mythological figures (creators and gods), rewards and punishments (physical actions), tests or trials, miscellaneous groups of motifs (which could hardly stand on their own), and character themes. Customs, traditions, and cultural practices such as the Bayanihan spirit, religious devotional practices, preservation of natural resources and environment, hospitality, storytelling, and a sense of community and friendship were identified. Both positive and negative traits and values were also manifested by the Biliran Ons. Similar studies and documentation of these folk stories could be conducted in other remote areas or places of Biliran and its adjacent provinces of Leyte and Samar to ensure timely collection and documentation, safeguarding and preserving for future generations what remains of these oral traditions and verbal arts.